Accurate identification of radicals by in-situ electron paramagnetic resonance in ultraviolet-based homogenous advanced oxidation processes - Long Chen; Duan, Jun; Du, Penghui; Weiliang Sun; Bo Lai; Liu, Wen (Water Research, 2022)
Accurate identification of radicals in advanced oxidation processes (AOPs) is important to study the mechanisms on radical production and subsequent oxidation-reduction reaction. The commonly applied radical quenching experiments cannot provide direct evidences on generation and evolution of radicals in AOPs, while electron paramagnetic resonance (EPR) is a cutting-edge technology to identify radicals based on spectral characteristics. However, the complexity of EPR spectrum brings uncertainty and inconsistency to radical identification and mechanism clarification. This work presented a comprehensive study on identification of radicals by in-situ EPR analysis in four typical UV-based homogenous AOPs, including UV/H2O2, UV/peroxodisulfate (and peroxymonosulfate), UV/peracetic acid and UV/IO4− systems. Radical formation mechanism was also clarified based on EPR results. A reliable EPR method using organic solvents was proposed to identify alkoxy and alkyl radicals (CH3C(=O)OO·, CH3C(=O)O· and ·CH3) in UV/PAA system. Two activation pathways for radical production were proposed in UV/IO4− system, in which the produced IO3·, IO4·, ·OH and hydrated electron were precisely detected. It is interesting that addition of specific organic solvents can effectively identify oxygen-center and carbon-center radicals. A key parameter in EPR spectrum for 5,5-dimethyl-1-pyrroline N-oxide (DMPO) spin adduct, AH, is ranked as: ·CH3 (23 G) >·OH (15 G) >IO3· (12.9 G) >O2·− (11 G) ≥·OOH (9–11 G) ≥IO4· (9–10 G) ≥SO4·− (9–10 G) >CH3C(=O)OO· (8.5 G) > CH3C(=O)O· (7.5 G). This study will give a systematic method on identification of radicals in AOPs, and shed light on the insightful understanding of radical production mechanism.
Keywords: Advanced oxidation processes; Electron paramagnetic resonance; Homogeneous; Radical; Ultraviolet